Single cell separation in microplates through micro patterning of “clickable” hydrogels - Alexander J. Straub; Frank D. Scherag; Mark-Steven Steiner; Thomas Brandstetter; Jürgen Rühe (Micro and Nano Engineering)
In this study, we report a novel approach for separating microspheres or cells on microstructured surfaces. These structures consist of μ-structured hydrogel coatings fabricated by photolithography on the bottoms of standard plastic microplate wells. The process is based on the deposition and subsequent irradiation of copolymers containing a hydrophilic main component and benzophenone moieties that can react with C, H groups during UV exposure through a photomask, a process known as “C,H insertion crosslinking” (CHic). The photolithographic process is used to generate an egg-box-like topography of the coating. Gravity, Brownian motion, and physical surface interactions drive particles or cells pipetted onto the surfaces to distinct locations on this topography so that after a short time these locations contain only one single particles or cells. We show that the presented technique enables the separation of thousands of objects as different as polymer microparticles or biological cells by simply adding a suspension to the coated wells of the microplate and wait for a short time (a few minutes). This strategy is quite general and not specific to a certain type of cell or microparticle and thus allow effortless separation of particles or cells.